Barriers to and constraints of acute peritoneal dialysis in acute kidney injury: A nationwide survey. Issue 1 (January 2022) - Treamtrakanpon, Worapot; Kanjanabuch, Talerngsak; Nopsopon, Tanawin; Chuengsaman, Piyatida; Dandecha, Phongsak; Boongird, Sarinya; Khositrangsikun, Kamol; Wongluechai, Laddaporn; Tatiyanupanwong, Sajja; Puapatanakul, Pongpratch; Srisawat, Nattachai; Eiam-Ong, Somchai; et al.
This national survey of barriers to and constraints of acute peritoneal dialysis (aPD) in acute kidney injury (AKI) was performed by distributing an online questionnaire to all medical directors of public dialysis units registered with the Nephrology Society of Thailand during September–November 2019. One hundred and thirteen adult facilities responded to the survey covering 75 from 76 provinces (99%) of Thailand. aPD was performed in 66 centres (58%). In facilities where aPD practice was available, the utilization rate was relatively low (<10 cases/year) and limited to specific conditions, including HIV seropositive patients, previous receiving dialysis education and plan and difficult vascular access creation. Only 9% of facilities performed aPD routinely, but interestingly all such units permitted bedside catheter insertion by the nephrologists or internists. The major constraints placed on aPD practice were PD catheter insertion competency, timely catheter insertion support and the medical supporting team's knowledge/competency deficits. aPD for AKI is underutilized in Thailand and limited by the inability to undertake timely PD catheter insertion and knowledge and competency deficits.